2015
DOI: 10.3906/tar-1410-73
|View full text |Cite
|
Sign up to set email alerts
|

Radiation, water, and nitrogen use efficiencies of Gossypium hirsutum L.

Abstract: Proper management of agro-based resources is a major baseline for precision agriculture (Lambin and Meyfroidt, 2011). In Pakistan, cotton (Gossypium hirsutum L.) is a widely cultivated fiber crop with limited available resources, namely selection of low-graded cultivars, imbalanced nutrient application, inadequate irrigation water supply, and so on, which contributes towards lower per capita yield production (Bibi et al., 2011;. Among the different resources, nitrogen is an important plant nutrient required in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…However, RUE is mainly affected by various abiotic factors in general (Kemanian et al, 2004), water (Ahmad et al, 2008), nutrients and particularly N (Muurinen and Peltonen-Sainio, 2006), and environments (Lecoeur and Ney, 2003). The RUE for various crops also varies at different growth stages (Zahoor et al, 2010;Ahmad et al, 2015). In a recent study, Ahmad et al (2012) reported that N split application as a top dressing along with a basal dose at sowing to C 3 winter cereals in saline soils under irrigated arid environments may be adopted as an alternate strategy to enhance NUE and RUE by decreasing the losses of N fertilizer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RUE is mainly affected by various abiotic factors in general (Kemanian et al, 2004), water (Ahmad et al, 2008), nutrients and particularly N (Muurinen and Peltonen-Sainio, 2006), and environments (Lecoeur and Ney, 2003). The RUE for various crops also varies at different growth stages (Zahoor et al, 2010;Ahmad et al, 2015). In a recent study, Ahmad et al (2012) reported that N split application as a top dressing along with a basal dose at sowing to C 3 winter cereals in saline soils under irrigated arid environments may be adopted as an alternate strategy to enhance NUE and RUE by decreasing the losses of N fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the productivity level of cereals, and particularly C 4 summer cereals, in Pakistan is very low compared to other growing countries (Ahmad et al, 2012). The inherent low productivity is the result of poor utilization of natural resources (land and radiation) and inputs (water and fertilizers), resulting in less resource-use efficiency (Mahmood et al, 2013;Ahmad et al, 2015), and climate change (Rehman et al, 2015). Ironically, farmers growing summer cereal crops use age-old agronomic practices, rather than adopting the best agricultural practices to harness higher resource-use efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Principally, it is essential to boost NUE through better approaches to increase RUE. So, split N application regimes result in considerable boost in NUE, production, and resultantly RUE by reducing losses and improving uptake [41]. It is a rising concern that most of the available or applied N is lost, thereby reducing NUE, which is just 29% for cereals in developing agrarian economies [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is the key constituent of agricultural inputs to maintain production of these cereals throughout their lifecycle [51][52][53][54] (Figure 3). Surplus N and/or N applied without splitting can be lost through pathways such as nitrification and volatilization [8,40,41] (Figure 1). Principally, it is essential to boost NUE through better approaches to increase RUE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation